Variable phenotype of Knobloch syndrome due to biallelic COL18A1 mutations in children. Issue 6 (November 2021) - Levinger, Nadav; Hendler, Karen; Banin, Eyal; Hanany, Mor; Kimchi, Adva; Mechoulam, Hadas; Meiner, Vardiella; Parag, Yoav; Sharon, Dror; Macarov, Michal; Yahalom, Claudia
Purpose: Knobloch syndrome is a rare, recessively inherited disorder classically characterized by high myopia, retinal detachment, and occipital encephalocele. Our aim is to report the clinical and genetic findings of four Israeli children affected by Knobloch syndrome. Methods: Retrospective study of four patients diagnosed with Knobloch syndrome, who underwent full ophthalmic examination, electroretinography, and neuroradiologic imaging. Genetic analysis included whole exome sequencing (WES) and Sanger sequencing. Results: The four patients included in this study had high myopia and nystagmus at presentation. Ocular findings included vitreous syneresis, macular atrophy, macular coloboma, and retinal detachment. One child had iris transillumination defects and an albinotic fundus, initially leading to an erroneous clinical diagnosis of albinism. Electroretinography revealed a marked cone-rod pattern of dysfunction in all four children. Brain imaging demonstrated none to severe occipital pathology. Cutaneous scalp changes were present in three patients. WES analysis, confirmed by Sanger sequencing revealed COL18A1 biallelic null mutations in all affected individuals, consistent with autosomal recessive inheritance. Conclusions: This report describes variable features in patients with Knobloch syndrome, including marked lack of eye pigment similar to albinism in one child, macular coloboma in two children as well as advanced cone-rod dysfunction in all children. One patient had normal neuroradiologic findings, emphasizing that some affected individuals have isolated ocular disease. Awareness of this syndrome, with its variable phenotype may aid early diagnosis, monitoring for potential complications, and providing appropriate genetic counseling.